Nontrivial Solutions for a System of Fractional q-Difference Equations Involving q-Integral Boundary Conditions - Yaohong Li; Jie Liu; Donal O’Regan; Jiafa Xu (Mathematics, 2020)
In this paper, we study the existence of nontrivial solutions for a system of fractional q-difference equations involving q-integral boundary conditions, and we use the topological degree to establish our main results by considering the first eigenvalue of some associated linear integral operators.